"My Surgical Success": Feasibility and Impact of a Single-Session Digital Behavioral Pain Medicine Intervention on Pain Intensity, Pain Catastrophizing, and Time to Opioid Cessation After Orthopedic Trauma Surgery—A Randomized Trial. (5th July 2022) - Ziadni, Maisa S.; You, Dokyoung S.; Keane, Ryan; Salazar, Brett; Jaros, Sam; Ram, Jesmin; Roy, Anuradha; Tanner, Natalie; Salmasi, Vafi; Gardner, Michael; Darnall, Beth D.
Abstract : BACKGROUND: Behavioral pain treatments may improve postsurgical analgesia and recovery; however, effective and scalable options are not widely available. This study tested a digital perioperative behavioral medicine intervention in orthopedic trauma surgery patients for feasibility and efficacy for reducing pain intensity, pain catastrophizing, and opioid cessation up to 3 months after surgery. METHODS: A randomized controlled clinical trial was conducted at an orthopedic trauma surgery unit at a major academic hospital to compare a digital behavioral pain management intervention ("My Surgical Success" [MSS]) to a digital general health education (HE) intervention (HE; no pain management skills). The enrolled sample included 133 patients; 84 patients were randomized (MSS, n = 37; HE, n = 47) and completed study procedures. Most patients received their assigned intervention within 3 days of surgery (85%). The sample was predominantly male (61.5%), White (61.9%), and partnered (65.5%), with at least a bachelor's degree (69.0%). Outcomes were collected at 1–3 months after intervention through self-report e-surveys and electronic medical record review; an intention-to-treat analytic framework was applied. Feasibility was dually determined by the proportion of patients engaging in their assigned treatment and an application of an 80% threshold for patient-reported acceptability. We hypothesized that MSS would result in greater reductions in pain intensity and pain catastrophizing after surgery and earlier opioid cessation compared to the digital HE control group. RESULTS: The engagement rate with assigned interventions was 63% and exceeded commonly reported rates for fully automated Internet-based e-health interventions. Feasibility was demonstrated for the MSS engagers, with >80% reporting treatment acceptability. Overall, both groups improved in the postsurgical months across all study variables. A significant interaction effect was found for treatment group over time on pain intensity, such that the MSS group evidenced greater absolute reductions in pain intensity after surgery and up to 3 months later (treatment × time fixed effects; F [215] = 5.23; P = .024). No statistically significant between-group differences were observed for time to opioid cessation or for reductions in pain catastrophizing ( F [215] = 0.20; P = .653), although the study sample notably had subclinical baseline pain catastrophizing scores (M = 14.10; 95% confidence interval, 11.70–16.49). CONCLUSIONS: Study findings revealed that a fully automated behavioral pain management skills intervention (MSS) may be useful for motivated orthopedic trauma surgery patients and reduce postsurgical pain up to 3 months. MSS was not associated with reduced time to opioid cessation compared to the HE control intervention.